Методи та засоби виявлення веб-додатків - Неізвєсна, М. Р. (ХНУРЕ, 2024)
This work is devoted to exploring methods and tools for detecting vulnerabilities in web applications, addressing the critical need for ensuring digital security. The detection and mitigation of vulnerabilities in web applications are paramount to safeguarding sensitive information and preventing unauthorized access or attacks. This study delves into diverse approaches such as active and passive scanning, code analysis, penetration testing, and fuzzing techniques, along with an overview of popular tools including Burp Suite, OWASP ZAP, Acunetix, Nessus, and Qualys.
Keywords: виявлення веб-додатків; Burp Suite